2006
DOI: 10.1039/b602989b
|View full text |Cite
|
Sign up to set email alerts
|

A novel ruthenium sensitizer with a hydrophobic 2-thiophen-2-yl-vinyl-conjugated bipyridyl ligand for effective dye sensitized TiO2 solar cells

Abstract: A hydrophobic and 2-thiophen-2-yl-vinyl-conjugated ruthenium complex, cis-Ru(dhtbpy)(dcbpy)(NCS)2 [dhtbpy = 4,4'-di(hexylthienylvinyl)-2,2'-bipyridyl; dcbpy = 4,4'-dicarboxy-2,2'-bipyridyl], was newly designed, synthesized and applied successfully to sensitization of nanocrystalline TiO2-based solar cells, giving a conversion efficiency of 9.5% under irradiation with AM 1.5 solar light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(78 citation statements)
references
References 17 publications
0
78
0
Order By: Relevance
“…[28] The ruthenium dye, cisRu(dhtbpy)(dcbpy)(NCS) 2 [dhtbpy¼4,4 0 -di(hexyl thienylvinyl)-2,2 0 -bipyridyl; dcbpy¼4,4 0 -dicarboxylic acid-2,2 0 -bipyridyl] (HRS-1), was reported previously. [29] Scheme 1 presents the chemical structures of the two dye molecules. Both of them contain one or two carboxylic acid groups for interlocking to the nc-TiO 2 surface through chemically bonding.…”
Section: Resultsmentioning
confidence: 99%
“…[28] The ruthenium dye, cisRu(dhtbpy)(dcbpy)(NCS) 2 [dhtbpy¼4,4 0 -di(hexyl thienylvinyl)-2,2 0 -bipyridyl; dcbpy¼4,4 0 -dicarboxylic acid-2,2 0 -bipyridyl] (HRS-1), was reported previously. [29] Scheme 1 presents the chemical structures of the two dye molecules. Both of them contain one or two carboxylic acid groups for interlocking to the nc-TiO 2 surface through chemically bonding.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic absorption spectra of the dye molecules measured in dimethylformamide (DMF) (Fig. 3a) ported previously, [8] it is close to that of HRS-1 (cis-di(thiocyanato)-4,4′-di(hexylthienylvinyl)-2,2′-bipyridine-4,4′-dicarboxylate-2,2′-bipyridine ruthenium(II)), [9] which uses thienylvinyl-conjugated bipyridine as an ancillary ligand. The electronic absorption spectra (in transmission mode) of SJW-E1, CYC-B3, and N3 assembled on the TiO 2 thin films ( Fig.…”
mentioning
confidence: 89%
“…45,46 It has been shown that Ru(II) polypyridyl complexes perform very efficiently in DSSCs. [47][48][49][50][51][52][53] The complexes used for DSSCs exhibit interesting photophysical properties, such as light absorption across the visible spectrum and long excited-state lifetimes. [54][55][56][57] These properties make this class of complexes highly interesting as potential PS in PDT.…”
Section: Introductionmentioning
confidence: 99%